Analisis Pengaruh Konten Edukasi Kesehatan di TikTok terhadap Kesadaran Hidup Sehat Generasi Z - Aulia Cahyani Putri; Dimas Pratama Nugraha; Nanda Aditya Saputra (Journal of Medical and Health Science, 2026)
Abstract The rapid growth of social media has transformed the dissemination of health information among Generation Z. TikTok has emerged as one of the most popular digital platforms for accessing information related to healthy lifestyles, nutrition, mental health, physical activity, and disease prevention. This study aims to analyze the influence of health education content on TikTok toward healthy lifestyle awareness among Generation Z using a Systematic Literature Review (SLR) approach. The study examined 20 national and international scholarly articles published between 2022 and 2025. Data analysis involved thematic identification, synthesis of findings, and evaluation of relationships between health content characteristics and improvements in health knowledge, attitudes, and behaviors. The findings indicate that TikTok health education content significantly contributes to increasing health awareness among Generation Z through concise, visual, interactive, and easily understandable information delivery. Content creator credibility, personal storytelling, visual information presentation, and TikTok’s recommendation algorithm enhance message effectiveness. Nevertheless, misinformation, limited digital health literacy, and entertainment-oriented content remain major challenges. This study concludes that TikTok has substantial potential as a health promotion medium for Generation Z when supported by high-quality content, active involvement of health professionals, and strengthened digital literacy initiatives.